Peran Kepemimpinan Kepala Madrasah dalam Mengembangkan Budaya Membaca Al-Quran - Nurul Arifin; Saipul Annur; Yuniar; Muhamad Fauzi; Junaidah (Didaktika: Jurnal Kependidikan, 2024)
Leadership is a crucial element in running an institution, but it is now difficult to find leaders as people tend to prioritize themselves and care less about the interests of others and the environment. This study aims to analyze the role of the Head of Madrasah in developing a culture of reading the Qur'an. This is a field study with a qualitative descriptive approach, using observation, interviews, and documentation for data collection. The data analysis involves collection, transcription, coding, categorization, theme identification, and interpretation to generate deep and meaningful insights. The study shows that the Head of Madrasah at MTs Nurul Ma’rifah OKI successfully developed a culture of reading the Qur'an through seven leadership roles (EMASLIM) according to the Minister of National Education Regulation No. 13 of 2007. The roles of the Head of Madrasah as Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator have been well implemented, making the culture of reading the Qur'an an excellent program. The main supporting factor is the appointment of several teachers as supervisors, which facilitates the program's implementation. However, the main obstacle is the lack of educational support from home, where the role of parents is very important.